Prevention of Autoimmune Diabetes in NOD Mice by Dimethyl Fumarate - Shiri Li; Nosratola D. Vaziri; Lourdes Swentek; Chie Takasu; Kelly Vo; Michael J. Stamos; Camillo Ricordi; Hirohito Ichii (MDPI AG, 2021)
Oxidative stress plays critical roles in the pathogenesis of diabetes. This study tested the hypothesis that by protecting β-cells against oxidative stress and inflammation, an Nrf2 activator, dimethyl fumarate (DMF), may prevent or delay the onset of type 1 diabetes in non-obese diabetic (NOD) mice. Firstly, islet isolation was conducted to confirm the antioxidative effects of DMF oral administration on islet cells. Secondly, in a spontaneous diabetes model, DMF (25 mg/kg) was fed to mice once daily starting at the age of 8 weeks up to the age of 22 weeks. In a cyclophosphamide-induced accelerated diabetes model, DMF (25 mg/kg) was fed to mice twice daily for 2 weeks. In the islet isolation study, DMF administration improved the isolation yield, attenuated oxidative stress and enhanced GCLC and NQO1 expression in the islets. In the spontaneous model, DMF significantly reduced the onset of diabetes compared to the control group (25% vs. 54.2%). In the accelerated model, DMF reduced the onset of diabetes from 58.3% to 16.7%. The insulitis score in the islets of the DMF treatment group (1.6 ± 0.32) was significantly lower than in the control group (3.47 ± 0.21). The serum IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-9, IL-12p70, IFN-γ, TNF-α, MCP-1 and CXCL16 levels in the DMF-treated group were lower than in the control group. In conclusion, DMF may protect islet cells and reduce the incidence of autoimmune diabetes in NOD mice by attenuating insulitis and proinflammatory cytokine production.